Tanggung Jawab Pengangkut Udara atas Kelambatan - Hasan Sidik (Intermestic: Journal of International Studies, 2016)
Air transportation is a crucial transportation mode in Indonesia due to its archipelagic geographical form. The problems arose from the delay of air carriers. This article aimed to discuss the problems of Indonesian air carriers from the international law perspective based on the literature studies of international conventions on air carrier industry. Some of the related conventions are: Chicago Convention 1944, Warsaw Convention 1929 that completed by the Den Haag Protocol 1955 and the Montreal Agreement 1966. Other than that the convention that regulates the airport safety from the sabotage and the regulations of Air Traffic Control. The analysis of these international laws therefore used to further analyze the responssse of Indonesia’s government on the delay of air carriers happened in 2015 by making the Government Regulation No. 89, 2015 on Air Carrier’s Delay. With the advancement of discussion and analysis on Indonesia’s government regulation for air carrier, therefore the responsssibility of air carriers’ delay is becoming clearer.